PERAN ORANG TUA DALAM PENDIDIKAN AGAMA ISLAM ANAK USIA REMAJA DI DUSUN SANTREN DESA MENDALAN WANGI KEC. WAGIR KAB. MALANG - Yudawil Choiri; Muhammad Hanif; Nur Hasan (VICRATINA, 2019)
This study aims to describe 1) juvenile religious behavior in adolescents and 2) the role of adolescent parents. The approach used is a qualitative approach, and the type of research is a case study. Data collection is done by observation method, interview method and documentation method. Technical data analysis uses 3 stages, namely data reduction, data presentation and conclusion. Check the validity of the data with an extension of participation, persistence of observation, and triangulation. The results of this study are; 1) religious behavior of adolescents in Santren Hamlet Mendalan Wangi Village, Wagir Sub-District, Malang Regency, many are religious and few are not religious. It is said to be religious because: teenage children are obedient to their parents, polite teenage children to the older, teenagers are active to mosques or prayer rooms, teenage children often attend religious activities, 2) parents in Santren Hamlet, Mendalan Wangi Village, Wagir District, Malang Regency, like; encourage or support any religious activity that is followed by adolescents, fostering personal adolescents by teaching ethics in daily life, teaching mahdhah worship and ghairu mahdhah worship, and advising teenagers with talk and accompanied by action.